PERBANDINGAN MOTIVASI, KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR BIOLOGI PESERTA DIDIK SMP ANTARA YANG DIBELAJARKAN DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DAN INQUIRY TERBIMBING - Harpina, Harpina; Jasruddin, Jasruddin; Azis, Andi Asmawati (UNM Journal of Biological Education, 2018)
This research aims at discovering: (1) the students’ learning motivation taught by utilizing Problem Based Learning model and Guided Inquiry model, (2) the students’ critical thinking ability taught by utilizing Problem Based Learning model and Guided Inquiry model, (3) the students’ learning result taught by utilizing Problem Based Learning model and Guided Inquiry model, (4) the differences of learning motivation, critical thinking ability, and students’ learning result taught by utilizing Problem Based Learning model and Guided Inquiry model. This research is a quasi experiment. The population is all grade VIII students in the first semester of SMPN 5 Bulukumba of academic year 2015/2016. The sampling technique used is random sampling technique by choosing two out of six classes. The taken classes for this research are grade VIII1 which is taught by utilizing Problem Based Learning model with the total of 24 students’ ang grade VIII2 which is taught by utilizing Guided Inquiry model with the total of 24 students. The results of research reveal that, (1) the students’ learning motivation taught by utilizing Problem Based Learning model is in very high category; whereas, the ones taught by utilizing Guided Inquiry model is in high category, (2) the students’ critical thinking ability taught by utilizing Problem Based Learning model and Guided Inquiry model are both in good category, but they have different mean score, (3) the students’ learning result of biology subject taught by utilizing Problem Based Learning model and Guided Inquiry model are both in good category, but they have different mean score in general, and (4) there are differences of learning motivation, critical thingking ability, and learning result of the students taught by utilizing Problem Based Learning model and Guided Inquiry model.